Motif, Tujuan dan Relasi Ziarah Kubur: Refleksi atas Tradisi dan Budaya Masyarakat Banten - Erdi Rujikartawi; Dini Fitriani (Tsaqofah, 2022)
This paper is part of the results of the research that has been carried out as well as the addition of various data and analysis from actifity pilgrims around the Banten area. There are some pilgrims who do not merely pray and ask forgiveness and safety from the almighty for themselves and the grave experts, but among the pilgrims there are other motives and goals and relationships in doing so. There is a problem as the center of the first discussion, what are the motives and goals of the pilgrim community in carrying out the rites or prayers that are said. Second, how is the relationship built between the pilgrim community and their beliefs, sacred places and the local community. The aim is none other than to obtain data and information as well as to conduct a critical study of the pilgrimage phenomenon so as to find answers to the motives, goals and relations of the pilgrimage community with the various traditions and cultures it undertakes. In guiding the validity of the data obtained and analyzed, interactive methods by reducing data, displaying data and verifying data are steps that are often carried out and then interpretation and analytical description of the data are carried out. The results obtained are that there are motives and goals of pilgrims regarding the fulfillment of their prayers and their various needs with various wasilah and tawashul karomah and wisdom from places and people who are considered to have advantages in their lifetime. the practices that are offered, kuncen as one of the policy-making actors in pilgrimage activities and local people who feel the positive impact of pilgrimage behavior and activities.